The Effectiveness of Natural Luffa Sponge As A Rainwater Filter - Shamsudin, Muhammad Norazmin; Ahmad, Noor Aliza (Recent Trends in Civil Engineering and Built Environment, 2022)
The use of natural materials in the field of construction is becoming increasingly popular these days. The product used in this study is a luffa sponge as the main ingredient in producing rainwater filter. In this study, luffa sponge would be studied for its effectiveness and determine the composite, physical, mechanical properties and ability of luffa sponge as a filter material. Several laboratory studies have been studied and analyzed from journals and articles to support the effectiveness of luffa sponge as a filter material. This test would able to determine the properties and behavior of the luffa sponge. At the end of the study, that luffa sponge is capable of being a rainwater filter material. In conclusion, natural materials can also be a good mechanism or tool for rainwater filters. To make a luffa sponge as an effectiveness material for rainwater filter, the luffa sponge needs a pre-treatment such as a chemically treated with NaOH solution to improve the composite characteristics.